Molecular epidemiology and antimicrobial resistance profiles of Klebsiella pneumoniae isolates from hospitalized patients in different regions of China - Li, Yan; Xie, Chonghong; Zhang, Zhijie; Liu, Jianhua; Chang, Hui; Liu, Yong; Qin, Xiaosong (Frontiers in Cellular and Infection Microbiology, 2024)
In this study, aimed to investigate the antimicrobial susceptibility of Klebsiella pneumoniae strains isolated from major hospitals in different regions of China during 2019-2020. A total of 26 hospitals in 19 provinces were included. Antimicrobial susceptibility tests were conducted on a total of 219 K. pneumoniae isolates, and the resistance rates of cefazolin, chloramphenicol, and sulfamethoxazole in the northwest were found to be lower than those in north and south of China. Meanwhile, we identified 45 carbapenem-resistant Klebsiella pneumoniae (CRKP) and 174 carbapenem-sensitive Klebsiella pneumoniae (CSKP) strains. There was a significant difference in antimicrobial resistance between them, and the CRKP isolates were characterized by the multiple-drug resistance phenotype.Further, we analyzed multilocus sequence typing (MLST) and carbapenemase resistant genes in CRKP. The most common sequence type (ST) was ST11 (66.7% of the strains). In addition, we detected 13 other STs which accounted for a small percentage. There were differences between ST11 and non-ST11 isolates in the resistance rate to amikacin, gentamicin, latamoxef, ciprofloxacin, levofloxacin, aztreonam, nitrofurantoin, fosfomycin, and ceftazidime/avibactam.In terms of molecular resistance mechanisms, the majority of the CRKP strains (71.1%, 32/45) harbored bla KPC-2 , followed by bla NDM (22.2%, 10/45). Strains harboring bla KPC or bla NDM genes showed different sensitivities to some antibiotics. In addition, there were also two strains with bla CTX-M and one with bla OXA-23 . Our analysis emphasizes the importance of surveilling carbapenem-resistant determinants and analyzing their molecular characteristics for better management of antimicrobial agents in clinical use.